Proxy indicators as measure of local economic dispositions in South Africa: an exploratory study - Barnard, Nico; Oranje, Mark (Department of Urban and Regional Planning, University of the Free State, 2014)
Despite rapid advances and sizeable middle-class formation in many African countries, development planning is still frustrated by the absence of reliable, relevant and up-to-date data. Even though South Africa is in a more fortunate position with regard to the availability of such data, it also has data gaps, notably with regard to informal economic activities in the rural areas of the country. This exploratory article engages the use of proxy indicators to provide cues as to the state of a local economy. The article explores the relationship between a number of potential proxy indicators and the national economy in order to identify those proxy indicators that mirror the national economy. An interview approach was used to test the identified indicators in three small towns in order to establish whether the nationally determined proxies reflect economic trends in practice. The six proxy indicators that closely mirrored the local economies of the three sampled towns represent a modest, introductory exploration of an area worthy of far more empirical research.

Ten spyte van die vinnige vooruitgang en groot middelklasvorming in baie Afrikalande, word ontwikkelingsbeplanning nog gefrustreer deur die afwesigheid van betroubare, relevante en resente data. Hoewel Suid-Afrika in ’n meer gunstige posisie is met betrekking tot die beskikbaarheid van sodanige data, het die land ook datagapings, veral met betrekking tot informele ekonomiese aktiwiteite in die landelike gebiede van die land. Hierdie verkennende artikel besigtig die gebruik van instaan (indirekte) aanwysers om leidrade te verskaf oor die toestand van ’n plaaslike ekonomie. Die artikel ondersoek die verhouding tussen ’n aantal potensiële instaanaanwysers en die nasionale ekonomie om die instaanaanwysers wat die nasionale ekonomie weerspieël, te identifiseer. ’n Onderhoud-benadering is gebruik om die geïdentifiseerde aanwysers in drie klein dorpies te toets om te bepaal of die nasionaal-bepaalde instaners die ekonomiese tendense in die praktyk weerspieël. Die ses instaanaanwysers wat die plaaslike ekonomieë van die drie steekproefdorpe die nouste weerspieël, verteenwoordig ’n beskeie, inleidende verkenning van ’n gebied waardig vir veel meer empiriese navorsing.

Ntle le ho nyoloha ha dipalo tsa malapa a kholang dichelete tse mahareng ka hara linaha tsa Afrika, merero ya tswelopele e ntse e sokola hoba ho se na tsebo ya sejoale joale hape e tshepahalang. Le ha Afrika Borwa e ntse tla ka koano hoba e na le tsebo ee, e ntse na le bothata hoba tsebo eo e na le diphahla, haholo holo tabeng tsa meruo ya mahaeng e se ka dibukeng. Ka hara dipatlisiso tsena, tshebediso ya disupisi tsa proxy ho fan aka ditsebiso tsa hore na moruo oa selehae na o tsamaea joang. Serapa sena se sheba dikamano mahareng a disupisi tsa proxy tse mmaloa le moruo oa naha. Mokhoa oa ditlhahlobo o sebedisitsoe ho hlahloba disupisi tse bonahetseng ka hara teropo tse nyane tse tharo ho bontsha hore na disupisi tsena na ehlile dia sebetsa. Disupisi tsa ts’eletseng tsa proxy ho feta dia hlokahala.
Keywords: Economic activites; Rural areas; Local economy